ANALISIS KRISIS KEPERCAYAAN GEN Z TERHADAP SELF-CLAIM HALAL FOOD VLOGGER KULINER NON-SERTIFIKASI - Misbahul Khoer; Ella Nurlaela; Acim Acim (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2026)
The phenomenon of unilateral halal claims (self-claiming halal) by food content creators on social media has sparked epistemic polemics and a crisis of trust among Generation Z Muslim consumers. This study aims to analyze the impact of the rise of these self-assumption-based halal claims on the perception of the legitimacy of non-certified culinary products and the crisis of trust experienced by Generation Z consumers. This study uses a qualitative approach with phenomenological methods and digital content analysis. Data was collected through in-depth interviews with twenty Generation Z Muslim consumer informants and systematic observations on several major social media platforms. The results show that unilateral claims from content creators have created information ambiguity and degraded consumers' halal literacy. Generation Z is experiencing a profound crisis of trust due to the contradiction between the visual narratives presented by content creators and formal regulations from official halal product assurance authorities. These findings indicate a behavioral shift in which Generation Z consumers have adopted a high level of digital skepticism and demand transparency of official certification in every food review content. In conclusion, the validity of halal information in the digital space cannot be replaced by the subjective authority of content creators, and this crisis of trust emphasizes the urgency of strengthening the regulation-based halal product assurance ecosystem to protect consumer rights. This research has contributed to the development of sharia marketing literature related to the dynamics of Muslim consumer behavior in the global digital era.